PENGARUH KESULITAN KEUANGAN, RISIKO LITIGASI, DAN LEVERAGE TERHADAP KONSERVATISME AKUNTANSI PADA PERUSAHAAN DAGANG YANG TERDAFTAR DI BURSA EFEK INDONESIA (2012-2014) - Anike Geovani Putri; Edfan Darlis; Lila Anggraini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aimed to examine the effect of financial distress, litigation risk, and leverage to accounting conservatism on trading companies that listed on the Indonesia Stock Exchange from 2012 to 2014. In this study, samples were taken by using purposive sampling method. The sample are trading companies that have been listed on the IDX in 2012-2014 and had been audited. Samples used were as many as 30 samples with criteria have been listed on the IDX in 2012-2014, financial statement published in the currency of rupiah, has been audited, accounting conservatism figured, and a time of 3 years in research period i.e 2012-2014. Analysis using the financial statement as a primary source of research. Technical analysis using multiple linear regression analysis with SPSS program. These results indicate that has no significant influence between Financial Distress and Accounting Conservatism on trading companies that have been listed on the IDX (2012-2014) with significant value 0,868. Litigation Risk variable has no significant influence to Accounting Conservatism on trading companies that have been listed on the IDX (2012-2014) with significant value 0,536. And Leverage variable has significant influence to Accounting Conservatism on trading companies that have been listed on the IDX (2012-2014) with significant value 0,066.Keywords: Financial Distress, Litigation Risk, Leverage, and Accounting Conservatism.